PENGARUH KREATIVITAS BELAJAR DAN PERSEPSI SISWA DALAM PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR IPS EKONOMI PADA SISWA KELAS VIII SMP N 2 BONJOL - Yusuf, Resky; Wahyuni, M.Pd, Sri; Susanti, S.Pd, Desi (Pendidikan Ekonomi, 2014)
AbstrakÂ This research done in junior high school 2 bonjol about The influence of creativity learning and studentâs perception in using learning media toward the result of studying IPS economic of the second grade students of junior high school 2 Bonjol. The purposes of this study are (1) to know what is the influence creativity learning toward the result of studying IPS economic subject of the eight grade students of junior high school 2 bonjol. (2) to know know what is the influence studentâs perception in using learning media toward the result of studying IPS economic of the second grade students of junior high school 2 Bonjol. (3) to know what is the influence of creativity learning and studentâs perception in using learning media toward the result of studying IPS economic of the second grade students of junior high school 2 Bonjol.Research design of this research is decriptive associative research. The population of this research is all of the eight grade students of junior high school 2 bonjol that is 135 students. Sample that is used 57 students with proportional random sampling method. This research is collected the primary data and secondary data, then analyzed the data statistically with descriptive analysis and inductive through multiple regression analysis that is using SPSS program version 16.0.The result of data analysis obtained that (3) there were the significance influence of creativity learning and studentâs perception in using learning media toward the result of studying IPS economic of the second grade students of junior high school 2 Bonjol. with sig amount 0,000, it means smaller than a= 0,05. (1) there was the significance influence of of creativity learning toward the result of studying IPS economic subject of the eight grade students of junior high school 2 BonjolÂ with sig amount 0,007 < 0,05 with the level of influence 0,128. (2) there was the significance influence studentâs perception in using learning media toward the result of studying IPS economic of the second grade students of junior high school 2 Bonjol. with sig amount 0,000 < 0,05 with the level of influence 0,548.Based on the result of this research above, it can be concluded that creativity learning and the use of learning media are two factors that is given the influence toward the result of studying IPS economic subject of the eight grade students of junior high school 2 Bonjol. So, the suggestion for the students in order to improve the creativity learning in the class and for the teachers in order to using the learning media well in learning process to increase the result of studying IPS economic subject of the eight grade students of junior high school 2 Bonjol.Â